2002
DOI: 10.1016/s0896-6273(02)00873-5
|View full text |Cite
|
Sign up to set email alerts
|

Selective Priming of Syntactic Processing by Event-Related Transcranial Magnetic Stimulation of Broca's Area

Abstract: It remains controversial whether Broca's aphasia is an articulatory deficit, a lexical-access problem, or agrammatism. In spite of recent neuroimaging studies, the causal link between cortical activity and linguistic subcomponents has not been elucidated. Here we report an experiment with event-related transcranial magnetic stimulation (TMS) to clarify the role of Broca's area, more specifically, the left inferior frontal gyrus (F3op/F3t), in syntactic processing. An experimental paradigm contrasted sentences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
49
2
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 27 publications
7
49
2
1
Order By: Relevance
“…Previous results (e.g. (Hashimoto and Sakai, 2002;Sakai et al, 2002)) have indicated a left-hemisphere specialization for sentence comprehension and processing, involving BA 44/45 and BA 8. However, a distinction has been made between explicit and implicit syntactic processing (Sakai et al, 2003), with BA 44/45 only recruited for explicit syntactic decisions.…”
Section: Discussionmentioning
confidence: 81%
“…Previous results (e.g. (Hashimoto and Sakai, 2002;Sakai et al, 2002)) have indicated a left-hemisphere specialization for sentence comprehension and processing, involving BA 44/45 and BA 8. However, a distinction has been made between explicit and implicit syntactic processing (Sakai et al, 2003), with BA 44/45 only recruited for explicit syntactic decisions.…”
Section: Discussionmentioning
confidence: 81%
“…For the first goal, it was hypothesized that the left inferior frontal cortex (Broca's area) known to be involved in native language syntactic processing would also be engaged for SLA. Broca's area (Brodmann's area [BA] 44 and BA 45) has been implicated in L1 syntactic processing by both lesion (Grodinsky, Pinango, Zurif, & Drai, 1999;Caramazza & Zurif, 1976) and imaging data (Muller and Basho, 2004;Musso et al, 2003;Sakai, Homae, & Hashimoto, 2003;Hashimoto & Sakai, 2002;Sakai, Noguchi, Takeuchi, & Watanabe, 2002;Grezes & Decety, 2001;Caplan, Alpert, Waters, & Oliviera, 2000;Caplan, Alpert, & Waters, 1999;Stromswold, Caplan, Alpert, & Rauch, 1996). Only recently has the role of Broca's area in the language acquisition process become the focus of brain imaging experiments.…”
Section: Introductionmentioning
confidence: 99%
“…However, these factors, if any, would have been canceled out in JP-JM, as well as in EP-EM, for the individual groups in the present study. On the other hand, it has been established recently that the left IFG is selectively involved in grammatical processing (Stromswold et al, 1996;Dapretto and Bookheimer, 1999;Kang et al, 1999;Embick et al, 2000;Friederici et al, 2000;Sakai et al, 2002;Suzuki and Sakai, 2003), independent of general cognitive factors such as task difficulty and short-term memory , and of unreal language rule usage (Musso et al, 2003). The present results suggest that the modulation of the left F3t/F3O activation is related to the sensitivity to specific language task demands rather than associated with cognitive development in general (Piattelli-Palmarini, 1980;Karmiloff and KarmiloffSmith, 2001).…”
Section: Discussionmentioning
confidence: 99%